Discrete element model calibration based on in situ measurements. Issue 5 (31st December 2021) - Keppler, Istvan; Bablena, Adrienn; Salman, Nihal D.; Kiss, Péter
Abstract : Purpose: Transportation of the measurement samples from their original place to the measurement site causes significant changes in their mechanical properties. The possibility of making in situ measurements helps to create more precise discrete element models. Design/methodology/approach: The possibility of using in situ modified vane shear test based measurement for the calibration of discrete element models is demonstrated in this work. Findings: The advantage of employing the adjusted vane test is that the values of in situ measurements can be used for the calibration. Originality/value: The procedure we present allows us to perform accurate discrete element calibration using data from on-site measurements that can be performed quickly and easily.